Aldehyde Dehydrogenase 2 Protects Against Post-Cardiac Arrest Myocardial Dysfunction Through a Novel Mechanism of Suppressing Mitochondrial Reactive Oxygen Species Production - Zhang, Rui; Liu, Baoshan; Fan, Xinhui; Wang, Wenjun; Xu, Tonghui; Wei, Shujian; Zheng, Wen; Yuan, Qiuhuan; Gao, Luyao; Yin, Xinxin; Zheng, Boyuan; Zhang, Chuanxin; et al. (Frontiers in Pharmacology, 2020)
Post-cardiac arrest myocardial dysfunction significantly contributes to early mortality after the return of spontaneous circulation. However, no effective therapy is available now. Aldehyde dehydrogenase 2 (ALDH2) enzyme has been shown to protect the heart from aldehyde toxicity such as 4-hydroxy-2-nonenal (4-HNE) and oxidative stress. In this study, we evaluated the effect of enhanced activity or expression of ALDH2 on post-cardiac arrest myocardial dysfunction and survival in a rat cardiac arrest model. Furthermore, we elucidated the underlying mechanisms with a focus on mitochondrial reactive oxygen species (ROS) production in a cell hypoxia/reoxygenation model. A total of 126 rats were used for the ALDH2 activation or cardiac overexpression of ALDH2 studies. Randomization was done 10 min before the respective agonist injection or in vivo gene delivery. We showed that enhanced activity or expression of ALDH2 significantly improved contractile function of the left ventricle and survival rate in rats subjected to cardiac arrest-cardiopulmonary resuscitation procedure. Moreover, ALDH2 prevented cardiac arrest-induced cardiomyocyte death from apoptosis and mitochondrial damage. Mechanistically, 4-HNE, a representative substrate of ALDH2, was dominantly increased in the hypoxia/reoxygenation-exposed cardiomyocytes. Direct addition of 4-HNE led to significantly augmented succinate accumulation and mitochondrial ROS production. Through metabolizing 4-HNE, ALDH2 significantly inhibited mitochondrial ROS production. Our findings provide compelling evidence of the cardioprotective effects of ALDH2 and therapeutic targeting this enzyme would provide an important approach for treating post-cardiac arrest myocardial dysfunction.